2020
DOI: 10.1101/2020.06.26.20135665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mycobacterium tuberculosis-specific T cell activation identifies individuals at high risk of tuberculosis disease

Abstract: Background: Provision of tuberculosis preventive treatment (TPT) to individuals with Mycobacterium tuberculosis (M.tb) infection (TBI) is a key strategy to reduce the global tuberculosis burden. Tuberculosis risk is significantly higher after recent compared to remote TBI. We aimed to define a blood-based biomarker, measured with a simple flow cytometry assay, to stratify different stages of TBI to infer risk of disease. Methods: Healthy adolescents were serially tested with QuantiFERON-TB Gold (QFT) to define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…90,91 In particular, HLA-DR expression on Mtb-specific CD4 T cells has shown promising sensitivity and specificity to discriminate between ATB and LTBI, 88,92 and it was also proposed as a potential prognostic marker for progression to active disease. [93][94][95] More recently, our work suggest that HLA-DR marks a subset of Mtb-specific CD4 T cells with an effector phenotype that have recently proliferated upon infection (Tippalagama et al manuscript in preparation).…”
Section: The Impac T Of T Cell D Ifferentiati On and Ac Tivati Onmentioning
confidence: 85%
See 1 more Smart Citation
“…90,91 In particular, HLA-DR expression on Mtb-specific CD4 T cells has shown promising sensitivity and specificity to discriminate between ATB and LTBI, 88,92 and it was also proposed as a potential prognostic marker for progression to active disease. [93][94][95] More recently, our work suggest that HLA-DR marks a subset of Mtb-specific CD4 T cells with an effector phenotype that have recently proliferated upon infection (Tippalagama et al manuscript in preparation).…”
Section: The Impac T Of T Cell D Ifferentiati On and Ac Tivati Onmentioning
confidence: 85%
“… ↑ HLA‐DR in Mtb ‐specific CD4 T cells compared to LTBI 88,92‐95 …”
Section: Cd4 T Cells and Their Importance In Mtb Infectionmentioning
confidence: 99%
“…Months, or years later, when an individual might present in clinic (94), blood immune cell levels may not accurately reflect events within the lung and therefore may not be a useful compartment to sample when delineating disease status or progression. This reflects a key HostSim prediction: recent efforts to identify events in the blood that may correlate with events in lung (23,24) may not be generalizable to every time point for every patient. This prediction is consistent with a recent NHP study that shows blood T-cell responses do not consistently reflect T-cell responses within granulomas (25).…”
Section: Discussionmentioning
confidence: 99%
“…This has limited the ability to use blood as a predictive measure for infection progression or diagnosis. However, recent association studies suggest ratios of antigen-specific CD4+ and CD8+ T cells within the blood of Mtb-infected hosts may help delineate LTBI from active TB (23,24). Conversely, NHP studies have shown that Tcell responses in the blood do not consistently reflect T-cell responses in granulomas (25,26).…”
mentioning
confidence: 99%
“…This study focused on understanding T cell immunobiology during acquisition of M.tb infection and the discovery of potential biomarkers to distinguish between recent and remote M.tb infection. Development of a simplified assay to identify such individuals, including validation in a test cohort and performance as a marker of disease progression, are beyond the scope of this paper and were reported separately (Mpande, under review, and [43]). This biomarker has the potential to identify individuals who are at high risk of progression and should receive tuberculosis preventive treatment, a key priority highlighted in the recent Global Tuberculosis Report [1], and differentiate them from those who are at low risk of progression and could be spared from treatment.…”
Section: Discussionmentioning
confidence: 99%